Analisis Hukum Ekonomi Syariah Terhadap Produk Simpanan Di BMT Kota Payakumbuh - Firdaus, Windra; Yanti, Novi; Helmi, Lika Akana; Syamsurizal, Syamsurizal; Wandi, Joni Indra (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
This study is motivated by the importance of compliance with Islamic economic law principles in savings products offered by Islamic financial institutions, such as Baitul Maal wa Tamwil (BMT). Previous research has largely focused on marketing aspects and the impact of savings products on financial institution revenue, but has not specifically addressed the implementation of wadi’ah and mudharabah contracts and the implications of unclear contracts on Sharia compliance. This study aims to analyze the application of Islamic economic law in savings products at BMT in Payakumbuh City, focusing on wadi’ah and mudharabah contracts. This research adopts a qualitative approach with a case study method. The study was conducted at BMT in Payakumbuh City from June to August 2024. Data sources consist of primary data obtained through in-depth interviews with BMT managers and customers, and secondary data in the form of contract documents used by BMT. Data collection techniques include interviews and document analysis, while data analysis uses qualitative descriptive methods with a non-statistical approach. To ensure data validity, member checking and source triangulation techniques were employed. The results indicate that the implementation of wadi’ah and mudharabah contracts in savings products at BMT in Payakumbuh City generally complies with Sharia principles, although there are some challenges related to contract clarity and communication with customers. This study is expected to contribute to the development of understanding of Islamic economic law and the practice of savings products at BMT, as well as increase public awareness in choosing Sharia-compliant financial products.